Glioma Stem Cell-Specific Superenhancer Promotes Polyunsaturated Fatty-Acid Synthesis to Support EGFR Signaling - Gimple, Ryan C; Kidwell, Reilly L; Kim, Leo J Y; Sun, Tengqian; Gromovsky, Anthony D; Wu, Qiulian; Wolf, Megan; Lv, Deguan; Bhargava, Shruti; Jiang, Li; Prager, Briana C; Wang, Xiuxing; et al. (Cancer discovery, 2019)
Glioblastoma ranks among the most aggressive and lethal of all human cancers. Functionally defined glioma stem cells (GSC) contribute to this poor prognosis by driving therapeutic resistance and maintaining cellular heterogeneity. To understand the molecular processes essential for GSC maintenance and tumorigenicity, we interrogated the superenhancer landscapes of primary glioblastoma specimens and GSCs. GSCs epigenetically upregulated ELOVL2, a key polyunsaturated fatty-acid synthesis enzyme. Targeting ELOVL2 inhibited glioblastoma cell growth and tumor initiation. ELOVL2 depletion altered cellular membrane phospholipid composition, disrupted membrane structural properties, and diminished EGFR signaling through control of fatty-acid elongation. In support of the translational potential of these findings, dual targeting of polyunsaturated fatty-acid synthesis and EGFR signaling had a combinatorial cytotoxic effect on GSCs. SIGNIFICANCE: Glioblastoma remains a devastating disease despite extensive characterization. We profiled epigenomic landscapes of glioblastoma to pinpoint cell state-specific dependencies and therapeutic vulnerabilities. GSCs utilize polyunsaturated fatty-acid synthesis to support membrane architecture, inhibition of which impairs EGFR signaling and GSC proliferation. Combinatorial targeting of these networks represents a promising therapeutic strategy. . .